2013
DOI: 10.1111/jpm.12091
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of physical exercises in developing certain fitness levels in children with hyperactivity

Abstract: The objectives of this study were to assess the effects of participating in regular physical activity on the fitness of children with hyperactivity. The study compared a sample of children who were assessed as hyperactive with the same number of children rated as non-hyperactive. The Conners' Rating Scale was used for hyperactivity evaluation, while fitness levels were assessed using a battery of six motor tests prior to and following the completion of the physical exercise programme. The findings indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
0
8
0
2
Order By: Relevance
“…As stated, some studies reporting beneficial effects of exercise interventions did not include any control condition (e.g., [44,47,124]) and thus may not rule out the possibility of practice effects. On the other hand, many studies compared an exercise intervention to a control group receiving no treatment and found positive effects on neurobehavioral performance, such as attention, working memory, inhibition, impulsivity, emotional functioning, motor skills, cognitive flexibility, or classroom behaviour [1,15,80,88,98,99,136].…”
Section: Long-term Interventionsmentioning
confidence: 99%
“…As stated, some studies reporting beneficial effects of exercise interventions did not include any control condition (e.g., [44,47,124]) and thus may not rule out the possibility of practice effects. On the other hand, many studies compared an exercise intervention to a control group receiving no treatment and found positive effects on neurobehavioral performance, such as attention, working memory, inhibition, impulsivity, emotional functioning, motor skills, cognitive flexibility, or classroom behaviour [1,15,80,88,98,99,136].…”
Section: Long-term Interventionsmentioning
confidence: 99%
“…Given that children with ADHD participate in more MVPA starting in early childhood, one would expect to see physical fitness advantages as well. However, a comparison of six tests of physical fitness between 18 preschool children in the highest 5% of ADHD symptoms in their school and 18 same-aged peers in the lowest 5% of ADHD symptoms in the school revealed that the low-symptom group evidenced better (though not statistically significantly better) performance across fitness tests at baseline (e.g., 50 more sit-ups in 60-seconds, sit-andreach average 60-cm greater) (Golubović, Milutinović, & Golubović, 2014).…”
Section: Studies In Early Childhood (Ages 4-6)mentioning
confidence: 94%
“…The only way to disentangle the benefits of these non-PA components of programs from the unique benefits of PA is to provide a comparable but sedentary attention control program. At least three trials of children with ADHD have used this design finding few significant differences between groups despite strong within-group gains in PA conditions (Bustamante et al, 2016;Geladé et al, 2017;Hoza et al, 2015). The latter study, Hoza et al (2015), is the largest and amongst the most rigorous studies in the literature, including 94 children with ADHD.…”
Section: Evidence From Observational Studiesmentioning
confidence: 99%
“…Los autores revelaron que los niños que formaban parte del grupo de síntomas del TDAH bajo presentaron mejor desempeño (aunque no fue estadísticamente significativo) en las pruebas de aptitud física (ej. 50 abdominales más en 60 segundos y un promedio de 60 cm más en la prueba de flexión de tronco sentado en comparación con los niños en el grupo de los síntomas del TDAH más alto) (Golubović, Milutinović, & Golubović, 2014).…”
Section: Estudios Durante La Niñez Temprana (4-6 Años)unclassified
“…La única forma de diferenciar los beneficios de programas que no incluyen AF de los beneficios de la AF exclusivamente es incluir un grupo control que reciba un programa sedentario. Al menos 3 estudios con niños y niñas con TDAH han utilizado este diseño y reportaron pocas diferencias significativas entre grupos, a pesar de las mejoras significativas reportadas en el grupo que recibió el programa de AF (Bustamante et al, 2016;Geladé et al, 2017;Hoza et al, 2015). Hoza y colegas (2015) realizaron el estudio más riguroso y con la mayor cantidad de niños y niñas con TDAH (N = 94) hasta el momento.…”
Section: Evidencia De Estudios De Intervenciones De Varias Semanasunclassified